CELLOPT: improved unit‐cell parameters for electron diffraction data of small‐molecule crystals. Issue 3 (29th April 2022) - Gruene, Tim; Clabbers, Max T. B.; Luebben, Jens; Chin, Jia Min; Reithofer, Michael R.; Stowasser, Frank; Alker, André M.
Abstract : Iterative optimization of the unit‐cell parameters improves the refinement of organic small‐molecule structures using electron diffraction data. Abstract : Electron diffraction enables structure determination of organic small molecules using crystals that are too small for conventional X‐ray crystallography. However, because of uncertainties in the experimental parameters, notably the detector distance, the unit‐cell parameters and the geometry of the structural models are typically less accurate and precise compared with results obtained by X‐ray diffraction. Here, an iterative procedure to optimize the unit‐cell parameters obtained from electron diffraction using idealized restraints is proposed. The cell optimization routine has been implemented as part of the structure refinement, and a gradual improvement in lattice parameters and data quality is demonstrated. It is shown that cell optimization, optionally combined with geometrical corrections for any apparent detector distortions, benefits refinement of electron diffraction data in small‐molecule crystallography and leads to more accurate structural models.